2006
DOI: 10.2353/ajpath.2006.050125
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Production by Tertiary Lymphoid Tissue Developing in Response to 2,6,10,14-Tetramethyl-Pentadecane (Pristane)

Abstract: Lymphoid neogenesis is associated with antibody-mediated autoimmune diseases such as Sjogren's syndrome and rheumatoid arthritis. Although systemic lupus erythematosus is the prototypical B-cell-mediated autoimmune disease, the role of lymphoid neogenesis in its pathogenesis is unknown. Intraperitoneal injection of 2,6,10,14-tetramethyl-pentadecane (TMPD, pristane) or mineral oil causes lipogranuloma formation in mice, but only TMPD-treated mice develop lupus. We report that lipogranulomas are a form of lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 61 publications
7
146
0
1
Order By: Relevance
“…6Aa), as reported previously (7,9) and similar to changes described in mice treated ip with adjuvant oil (26). Isolated granulomas were also seen in liver (Fig.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…6Aa), as reported previously (7,9) and similar to changes described in mice treated ip with adjuvant oil (26). Isolated granulomas were also seen in liver (Fig.…”
Section: Resultssupporting
confidence: 71%
“…The i.p. vaccination in salmon induces chronic granulomatous inflammation similar to the peritoneal granuloma of rodents with adjuvant-oil induced lupus (26). Lymphoid neogenesis in affected tissues of various human autoimmune diseases, such as synovium in rheumatoid arthritis, thyroid gland in chronic thyroiditis, and salivary gland in Sjögren's syndrome, has been well described (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blanco et al (32) showed that up to 60% of IFN␣ production in the peripheral blood of lupus patients may come from cells other than plasmacytoid DCs. Myeloid DCs and monocyte-derived DCs could serve as alternative IFN␣-producing cells, as hinted at by studies in a mouse model 810 YAN ET AL of pristane-induced lupus (33). In the present study, the term of "IFN␣-producing APCs" was used to represent such cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Under the same experimental conditions, a number of mineral oils acted as adjuvants by promoting elevated concentrations of autoantibodies. While injection of 0.5 ml n-hexadecane, squalene or incomplete Freund's adjuvant induced autoantibody responses to nuclear antigens in female Balb/c mice, medicinal mineral oils (MO-HT, MO-S (C 20 -C 40 ), MO-F (C 15 -C 40 )) induced lipogranulomas, but only selected anti-nuclear autoantibodies and no clinical manifestations (Satoh, 2003;Kuroda et al, 2004, Nacionales et al, 2006.…”
Section: Animal Experimentsmentioning
confidence: 99%